Analgesic effect of erector spinae plane block in lumbar spine surgery: A systematic review and meta-analysis of randomised controlled trial / Lee Tzi Sen - Lee , Tzi Sen (2024)
Introduction: The use of ESP block has gained popularity in multiple types of surgeries which include lumbar spine surgeries. It is a relatively new technique in lumbar spine surgery and its advantages includes analgesic effect and also reducing opioid consumption, hence promoting ERAS. The purpose of this meta-analysis is to evaluate the analgesic effect of ESP block in lumbar spine surgery. Method: Randomized controlled trials of ESP block in lumbar spine surgery was searched in Pubmed and clinicaltrial,gov. Data was selected and was reviewed by two author which included a total of 7 RCTs. Result: Meta-analysis suggested that there is a statistical significant difference in ESP block providing lower pain scores at rest at 0 hour (MD, -1.60; 95% CI, -2.74 to -0.46; I2 = 93%; P = 0.006) and 24 hours (MD, -0.54; 95% CI, -0.98 to -0.10; I2 = 70%; P = 0.02) postoperatively as compared to patients who do not receive ESP block. There is no statistically significant difference in postoperative pain scores between patients who receive and did not receive ESP block at 4 hours (MD, -0.97; 95% CI, -2.21 to 0.27; I2 = 94%; P = 0.13) and 12 hours (MD, -1.28; 95% CI, -2.54 to -0.03; I2 = 96%; P = 0.05). It also showed that patient with ESP block had lower 24-h opioid consumption (MD, -50.95; 95% CI, -68.09 to -33.80; I2= 100%; P < 0.00001) and significant reduction in incidence of PONV (RR, 0.39; 95% CI, 0.20 to 0.77; I2 = 55%; P =0.007). Conclusion: Our meta-analysis found that ESP block proven to be effective in reducing post operatively pain score, post operative opioid consumption and PONV in lumbar spine surgery. However, due to high heterogeneity, further studies need to be carried out to determine the efficacy.